Assessing the Grip of Solar Energy Systems on Environmental Sustainability- A Review - Srivastava, Shreya; Behera, Ajit; Biswal, Ramakrishna (Micro and Nanosystems, 2022)
A sustainable energy production system fulfills its goal while being environmentally, socially, and technically sound. The intermittent availability and viability of renewable energy makes this vision a gradual and long-suffering process. In the rapid result-oriented economy, concerns regarding the environment are treated with desperate solutions that may add fuel to the fire. Although substantial research has been going on in the development of emerging technologies and refinement of established systems, we need to be reminded of the larger goal in mind: a benign and sustainable environment. Closing a door on a problem and not opening several new ones is what we must yearn to achieve. Renewable energy systems and their utility may unintentionally harm a different subset of the ecosystem. Solar energy systems are a more recent candidate with a high annual growth rate and thus, are still in the nascent stage to realise the bruised potential of the technology. By 2050, 60 million tons of solar waste will be produced if it is not resolved efficiently. To achieve environmental sustainability, it is imperative to work towards recycling redundant systems, establishing producer responsibility, fulfilling social needs and optimising future technology. By integrating aspects of the research on solar energy systems, their environmental risks, and their potential to create a sustainable ecosystem, this review article attempts to cater to environmental decision making and direct the eventual research and analysis towards their original unified objective.
Keywords: CSP systems